Distance Education and its Relation to the New Information and Communication Technologies - Marianela Falcón Villaverde (Medisur, 2013)
Most American and European universities have implemented distance education supported by the new information and communication technologies. Cuba has gradually joined this group, especially in higher education. Among the pioneer universities which have used this mode of education in Cuba, it is important to mention the Distance Education Department of the University of Havana, Marta Abreus University of Las Villas, Santiago de Cuba University, the Infomed Virtual Health University, the Higher Institute of International Relations, CITMA and other teaching institutions of the country. The University of Medical Sciences in Cienfuegos also uses this form of education through the website of the Virtual Health University, which provides online courses for undergraduate and postgraduate students. We considered necessary to review the Internet literature on this subject, presenting the main theories on which distance education is based, as well as to acknowledge the importance of the new information and communication technologies in distance education.